PERSEPSI PEMILIH PEMULA TERHADAP KINERJA PEYELENGGARA PEMILU PRESIDEN TAHUN 2014 - Muhammad Solihin; Tree Setiawan Pamungkas; Jhon Roi Tua Purba (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan ilmu Politik Universitas Riau Kep, 2017)
The rapid population of beginner voters in Indonesia than in 2004-2009 should be a calculation in influencing election results. Perception of beginner voters on the performance of electoral institutions in a sense it is important to be discussed because of the independence and professionalism an important factor general election success.This study uses the quantitative research survey. Data collection techniques by questionnaire. The sampling technique is done with strafied random sampling technique. The survey conducted on students at nine universities in YogyakartaResults from this study: First, Knowledge voters on electoral institutions. Voters who do not know Bawaslu that as many as 49.7 percent of respondents. As for the KPU as much as 65.1 percent of voters know; Second, the level of confidence in electoral institutions quite good 57.2 percent of voters believe; Third, the perception of the neutrality of electoral institutions 50.5 percent; and Fourth, the Electoral Institute of Professionalism 48.1 percent of voters declared